Optimizing the Role of the Makassar Regional V Airport Authority Office on Supervision of Land-Side Facilities at Sultan Hasanuddin International Airport Makassar - Alfriona Marta Madile; Ristiani Ristiani (CV. Rayyan Dwi Bharata, 2023)
The Airport Authority has the authority to carry out and carry out supervision to ensure flight safety and service and can be expected to fulfill its duties as executor of regulation, supervision and control of the airport area both on the land side and on the air side in accordance with established procedures. One of the roles and/tasks of the Airport Authority in the Field of Airport Services and Operations is supervision of land-side facilities, which aim to support services and maintain safety and security on the airport landside. Supervision and control of airport authorities must be optimized so that service, security and aviation safety can be carried out. The research method used in this research is descriptive with a qualitative approach and the type of research is a case study. Qualitative in this study is a process that produces descriptive data in the form of written words from informants and/or objects studied or observed. So that in the research that has been carried out, the researcher describes how the results of optimizing supervision carried out by the airport authority office on the land side facilities at Sultan Hasanuddin Makassar International Airport, as well as the obstacles and how to solve them. The results of the study show that the optimization efforts related to personnel in the field of Airport Service and Operations (P2BU) can be said to be optimal because the airport inspector reacts according to the constraints faced. This is done by rearranging the time with the airport operator for inspection, then carrying out intensive communication with other airport inspector friends, by changing personnel and/or changing supervision times, as well as notes during the supervision process the replaced inspector must inform detail to the inspector on duty. The results of the supervision in the form of inspections, monitoring (monitoring) and surveillance (observation) are reported to the airport directorate, in the form of minutes and reports on the results of supervision. The obstacles faced by airport inspectors are in terms of conditions, equipment and budget when the supervision is carried out.